2017
DOI: 10.1002/bit.26252
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ethanol production from crystalline cellulose via optimizing cellulase ratios in cellulolytic Saccharomyces cerevisiae

Abstract: Crystalline cellulose is one of the major contributors to the recalcitrance of lignocellulose to degradation, necessitating high dosages of cellulase to digest, thereby impeding the economic feasibility of cellulosic biofuels. Several recombinant cellulolytic yeast strains have been developed to reduce the cost of enzyme addition, but few of these strains are able to efficiently degrade crystalline cellulose due to their low cellulolytic activities. Here, by combining the cellulase ratio optimization with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…3A and 2A, same strain and inoculum quantity). Furthermore, it was observed that increasing the inoculum from 50 to 100 g wet cells/L, an inoculum concentration in the order of magnitude of the normally reported for CBP strains [8,36], improved the overall process ( Fig. 3A and 3B) and increased the ethanol titer from 8.15 to 11.1 g/L (corresponding to an increase of 36 % in ethanol concentration) and the ethanol yield from 0.240 to 0.328 g per g of potential sugar (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…3A and 2A, same strain and inoculum quantity). Furthermore, it was observed that increasing the inoculum from 50 to 100 g wet cells/L, an inoculum concentration in the order of magnitude of the normally reported for CBP strains [8,36], improved the overall process ( Fig. 3A and 3B) and increased the ethanol titer from 8.15 to 11.1 g/L (corresponding to an increase of 36 % in ethanol concentration) and the ethanol yield from 0.240 to 0.328 g per g of potential sugar (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…When the resulting strain was assessed by ethanol fermentation from 20 g/L PASC, it has successfully obtained 4.3 g/L ethanol in 72 h with an ESCY of~44% where the titer was about 1.7 times higher when compared to the strain not expressing the cellodextrin utilization pathway [68]. Another case where two exoglucanases from T. emersonii and C. lucknowense, a T. reesei endoglucanase (EG2), and an A. aculeatus β-glucosidase (BGL1) were co-displayed using the cocktail delta-integration strategy on the yeast surface by Liu, et al [69] in the attempt to obtain a highly cellulolytic strain. The transformants were then subjected to a high-throughput screening (HTS) methodology for the selection of the strain that exhibits high cellulolytic activity.…”
Section: Dysd Strategy For Cellulosic Bioethanol Fermentationmentioning
confidence: 99%
“…The transformants were then subjected to a high-throughput screening (HTS) methodology for the selection of the strain that exhibits high cellulolytic activity. The resulting strain that exhibits the highest cellulolytic activity was subjected to ethanol fermentation from Avicel (non-treated crystalline cellulose) and it obtained~3 g/L of ethanol within 96 h with an ESCY of~60% (highest reported ethanol yield for from avicel) [69].…”
Section: Dysd Strategy For Cellulosic Bioethanol Fermentationmentioning
confidence: 99%
“…This pretreatment is necessary since most of the bacteria and yeast species do not present considerable cellulolytic activity at the industrial level. Efforts have been made in creating recombinant strains which are capable of hydrolyzing the biomass and fermenting the sugar monomers in an one‐step process . Filamentous fungi, such as Trichoderma reesei , Penicillium echinulatum , Aspergillus niger , and Humicola grisea are the main source of cellulases and hemicellulases genes for heterologous expression in Saccharomyces cerevisiae and Pichia pastoris .…”
Section: Introductionmentioning
confidence: 99%
“…biomass and fermenting the sugar monomers in an one-step process [3]. Filamentous fungi, such as Trichoderma reesei, Penicillium echinulatum, Aspergillus niger, and Humicola grisea are the main source of cellulases and hemicellulases genes for heterologous expression in Saccharomyces cerevisiae and Pichia pastoris [4].…”
mentioning
confidence: 99%